Mediating role of educational environment in the relationship between workload and generic skills of nursing students in Vietnam - Nguyen, Thi Hoa Huyen; Bui, Hien Thi; Phan, Hong Anh; Hoang, Hue Thi; Hoang, Van Lan (Frontiers in Education, 2023)
Students' learning experiences are considered useful indicators to evaluate the effectiveness of teaching in tertiary education. This study aimed to examine whether the educational environment is able to mediate the relationship between student workload and generic skills. From November 2021 to January 2022, a cross-sectional study including 1347 nursing students from ten nursing schools across Vietnam was conducted. The results showed that the total score of the students' workload and the generic skills were 3.25 ± 0.59 and 3.84 ± 0.56 (possible score: 1-5), respectively. These findings indicated students were at an "agree" level with statements of "the sheer volume of work to be got through in this course means you can't comprehend it" and "as results of doing this course, I feel more confident about tackling unfamiliar problem". Most nursing students rated the educational environment at levels of "more positive educational environment" (N=1018, 75.58%) with a total score of 120.75 ± 20.78 (possible score: 0-200). The educational environment was identified as a mediator in the relationships between the workload and the generic skills. The direct effect for workload was -0.00035 which was not significant (p=0.987) with the generic skills. The indirect effect of workload that passes through the educational environment was -0.07 and is also statistically significant, at p= 0.002. From these results, the study suggests that, to enhance students' generic skills, it is necessary to instruct students in efficient learning strategies to help them manage their academic workload, particularly during unexpected situations such as the COVID-19 pandemic. Additionally, despite the occurrence of a high level of student workload, nursing schools could focus on efficient tactics and interventions to improve the educational environment, which subsequently helps to improve students' outcomes.